STUDY OF PHYSICAL DEVELOPMENT AND FUNCTIONAL STATE OF SCHOOLCHILDREN'S ORGANISM (Academia Science Repository, 2023)
Indicators of physical development are the most objective and reliable criteria for the favorable or unfavorable influence of various factors on the growth and development of the body. The physical development of a person is assessed, first of all, by the state of the musculoskeletal system, correlating body length (height), and weight and chest circumference. We set the following goal: to study the physical development and functional state of 14-15 year old schoolchildren.